Development And Implementation of a Novel Code Family for Optical Code Division Multiple Access Systems - Syed Junid, Syed Alwee Aljunid (2005)
Future telecommunication systems and networks are expected to provide a variety of integrated broadband services to the customers. There has been a tremendous interest in applying Code Division Multiple Access (CDMA) techniques to fiber optic communication systems. This technique is one of the multiple access schemes that is becoming popular because of the flexibility in the allocation of channels, ability to operate asynchronously, enhanced privacy and increased capacity in bursty networks. The performance of any Optical CDMA (OCDMA) system strongly depends on the codes properties. In this study we introduce a new code for Optical CDMA namely Double Weight Code family (DW). Double Weight Code (DW) has a basic fixed weight of 2 and exists for every natural number. The DW codes possess ideal cross correlation properties, which have important characteristics in OCDMA systems since these can eliminate multiple access interference (MAI) and reduce noise. Also proposed in this study, a Modified Double-Weight (MDW) code, which is a variation of DW code family that can have a variable weight greater than two. The MDW code possesses ideal crosscorrelation properties and exists for every natural number too. It is shown through simulations, theoretical analysis and partially by the experiments that the transmission performance of DW code family is significantly better than that of existing codes such as Modified Frequency Hopping code (MFH) and Hadarnard code. The performance of DW code family, MFH and Hadamard codes were simulated using commercial simulation software, OptiSystem Version 3.0. The performance of the systems was characterized by referring to the bit error rate (BER) and the eye patterns. DW code family has shown superior performance compared to other OCDMA codes. The simulated eye pattern of one of the four MDW coded carriers running at lOGbps over a cornrnunication-standard fiber shows a good quality transmission at the BER of 10 -12 as opposed to only 1o ' ~an d 1o 4 for Hadamard and MFH codes. In optical CDMA systems, the detection process affects the design of transmitters and receivers. Cross-correlation functions are generated which creates Multiple Access Interference (MAI) and this will degrade the system performance. MA1 can be reduced by using subtraction techniques. The most common subtraction technique is the complementary subtraction technique and also known as balanced detection technique. In this thesis, we also introduce a new approach called AND subtraction technique. This method rejects unwanted signals that interfere with the original signals. Furthermore, the purpose of this new subtraction technique is to reduce the receiver complexity and increase system performance. It has been shown through theoretical analysis, simulation and experimental work, the performance of the system with AND subtraction technique can be improved significantly. Based on the theoretical analysis, BER as good as 10-l2is achieved at the bit rate of 622 Mbps over 70 km distance.